Biofumigation With Pellets of Defatted Seed Meal of Brassica carinata: Factors Affecting Performance Against Phytophthora nicotianae in Pepper Crops - Serrano-Pérez, Paula; De Santiago, Ana; Rodríguez-Molina, María del Carmen (Frontiers in Sustainable Food Systems, 2021)
Phytophthora nicotianae causes root and crown rot disease in open field paprika pepper crops of Extremadura (western Spain). A field experiment was established during spring, as it is compatible with the crop cycle in this region, to evaluate the effects of biofumigation with pellets of Brassica carinata defatted seed meal, at the rate recommended by the manufacturer (3 tons ha-1), on the survival and infectivity of P. nicotianae chlamydospores inoculum. Furthermore, three biofumigant rates (3, 6 and 20 tons ha-1) were assayed in laboratory experiments with natural soil inoculated with chlamydospores. In the field trial, the incorporation of pellets at 3 tons ha-1 did not produce remarkable changes in soil enzyme activity or soil properties. In both the field and laboratory tests, survival and infectivity in the biofumigated treatment at 3 tons ha-1 did not differ from those in the untreated control. On the contrary, the same rate added to autoclaved soil completely suppressed the inoculum, suggesting that the soil microbiota degrades B. carinata pellets before being effective against P. nicotianae. Increasing the recommended rate to 6 tons ha-1 decreased inoculum survival in the laboratory test and 20 tons ha-1 completely inhibited the inoculum, although the economic value of such a high rate application is a factor to be assessed.